Human agency and sociolinguistic citizenship in contemporary Galicia: Ideologies, management and practices towards linguistic revitalisation - Nandi, Anik; Vázquez-Fernández, Martín (Boletín de Filología, 2023)
In the contemporary era of globalization, there is persistent pressure on minority languages from the dominant languages, partly because many minority language speakers find shifting to a dominant one a profitable choice. Language policy scholarship through the past decades, whether top-down or bottom-up, also registers that many minority speakers intend to preserve or reclaim their languages as active agents through everyday interactions and the transmission of the language within the home or in the community despite these external pressures. Based on Stroud’s (2018) analytical framework of ‘sociolinguistic citizenship’ that investigates questions of power, ideology, legitimacy and marginalisation, this paper examines the multifarious layers between governmental language policies and how they are interpreted, implemented or negotiated by a wide range of social actors (e.g., parents, students, teachers, activists), revealing ideological spaces for the use or non-use of Galician, an official minority language spoken in a bilingual community of northwestern Spain. Using various qualitative research tools, including field observations, interviews and focus groups, we demonstrate how these actors become policy intermediaries on the ground and argue that their under-the-radar participation in the policy discourse may appear extremely intermittent and ad hoc, but their microcosmic interrogation of the dominant Castilian discourse through individual actions, when translates into collective mobilisations can lead to bottom-up language policies.